Septic Arthritis in a Renal Transplant Patient - Stacy Ploom BS; Marcus Cooley MD; Avish Nagpal MD; Dubert M. Guerrero MD (SAGE Publishing, 2023)
Blastomycosis is a rare endemic fungal infection caused by the dimorphic fungus Blastomyces dermatitidis. It is more likely to occur in persons living in areas of the United States and Canada, which border the Ohio and Mississippi River Valleys and the Great Lakes region. Most infections are localized to the lungs, often presenting as acute or chronic pneumonia. Occasionally, patients progress to develop disseminated disease and extrapulmonary infections. Blastomycosis tends to be misdiagnosed initially at clinical evaluation as it is rare and may resemble other common conditions. We present a case of a 78-year-old immunosuppressed renal transplant patient who was suspected of having gout but eventually was diagnosed with an unusual presentation of septic arthritis of the ankle secondary to blastomycosis.